ANTESEDEN VARIABEL PADA TURNOVER INTENTION KARYAWAN PT PATRA JASA - Andita Jasmeen Pratama; Christine Winstinindah Sandroto (Prosiding Working Papers Series In Management, 2018)
This study aims to examine antecedent variables on turnover intention of PT PATRA JASA employees, with independent variables are commitment organizational, job satisfaction, person organization fit and work stress factor, while the independent variable which is the intention of turnover.Data were collected by distributing questionnaires to 60 employees of PT PATRA JASA Jakarta. Sampling method used is convenience sampling. The results show that partially commitment organization has negative significant effect on turnover intention, job satisfaction has negative significant effect on turnover intention, person organization fit has negative significant effect on turnover intention, and work stress factor has positive significant effect on turnover intention. Simultaneously commitment organization, job satisfaction, person organization fit, and work stress factor variables have a significant effect on turnover intention of employee in PT PATRA JASA.  Keywords:  commitment organization, job satisfaction, person organization fit, work stress, and turnover intention